A signaling mucin at the head of the Cdc42- and MAPK-dependent filamentous growth pathway in yeast - Cullen, Paul J. (Cold Spring Harbor Laboratory Press, 2004)
Signaling molecules such as Cdc42 and mitogen-activated protein kinases (MAPKs) can function in multiple pathways in the same cell. Here, we propose one mechanism by which such factors may be directed to function in a particular pathway such that a specific response is elicited. Using genomic approaches, we identify a new component of the Cdc42- and MAPK-dependent signaling pathway that regulates filamentous growth (FG) in yeast. This factor, called Msb2, is a FG-pathway-specific factor that promotes differential activation of the MAPK for the FG pathway, Kss1. Msb2 is localized to polarized sites on the cell surface and interacts with Cdc42 and with the osmosensor for the high osmolarity glycerol response (HOG) pathway, Sho1. Msb2 is glycosylated and is a member of the mucin family, proteins that in mammalian cells promote disease resistance and contribute to metastasis in cancer cells. Remarkably, loss of the mucin domain of Msb2 causes hyperactivity of the FG pathway, demonstrating an inhibitory role for mucin domains in MAPK pathway activation. Taken together, our data suggest that Msb2 is a signaling mucin that interacts with general components, such as Cdc42 and Sho1, to promote their function in the FG pathway.